Visuospatial anatomy comprehension: The role of spatial visualization ability and problem‐solving strategies. Issue 4 (10th October 2013) - Nguyen, Ngan; Mulla, Ali; Nelson, Andrew J.; Wilson, Timothy D.
<x xml:space="preserve">Abstract</x> The present study explored the problem‐solving strategies of high‐ and low‐spatial visualization ability learners on a novel spatial anatomy task to determine whether differences in strategies contribute to differences in task performance. The results of this study provide further insights into the processing commonalities and differences among learners beyond the classification of spatial visualization ability alone, and help elucidate what, if anything, high‐ and low‐spatial visualization ability learners do differently while solving spatial anatomy task problems. Forty‐two students completed a standardized measure of spatial visualization ability, a novel spatial anatomy task, and a questionnaire involving personal self‐analysis of the processes and strategies used while performing the spatial anatomy task. Strategy reports revealed that there were different ways students approached answering the spatial anatomy task problems. However, chi‐square test analyses established that differences in problem‐solving strategies did not contribute to differences in task performance. Therefore, underlying spatial visualization ability is the main source of variation in spatial anatomy task performance, irrespective of strategy. In addition to scoring higher and spending less time on the anatomy task, participants with high spatial visualization ability were also more accurate when solving the task problems. Anat Sci Educ 7: 280–288. © 2013 American Association of Anatomists.